The history and growth of judicial review. Volume 1, The G-20 common law countries and Israel - Calabresi, Steven G. (New York, NY : Oxford University Press, 2021)
This two-volume set examines the origins and growth of judicial review in the key G-20 constitutional democracies, which include the United States, the United Kingdom, France, Germany, Japan, Italy, India, Canada, Australia, South Korea, Brazil, South Africa, Indonesia, Mexico, and the European Union, as well as Israel. The volumes consider five different theories, which help to explain the origins of judicial review, and identify which theories apply best in the various countries discussed. They consider not only what gives rise to judicial review originally, but also what causes of judicial review lead it to become more powerful and prominent over time. Volume One discusses the G-20 common law countries and Israel.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 16, 2021).
Keywords: Judicial review -- History; Law; Laws of specific jurisdictions & specific areas of law